Correlation between the sulfamethoxazole-trimethoprim resistance of Shigella flexneri and the sul genes - Ma, Quanping (Medicine (Baltimore), 2021)
The aim of this study was to discuss the correlation between the sulfamethoxazole-trimethoprim resistance of Shigella flexneri (S. flexneri) and the antibiotic resistance genes sul1, sul2, and sul3 and SXT element. From May 2013 to October 2018, 102 isolates of S. flexneri were collected from the clinical samples in Jinan. The Kirby–Bauer (K-B) test was employed to determine the antibiotic susceptibility of the S. flexneri isolates. The antibiotic resistance rate was analyzed with the WHONET5.4 software. The isolates were subject to the PCR amplification of the sul genes (sul1, sul2, and sul3) and the SXT element. On the basis of the sequencing results, the correlation between the sulfamethoxazole-trimethoprim resistance of the S. flexneri isolates and the sul genes was analyzed. The antibiotic resistance rates of the 102 S. flexneri isolates to ampicillin, streptomycin, chloramphenicol, tetracycline, and sulfamethoxazole-trimethoprim were 90.2%, 90.2%, 88.2%, 88.2%, and 62.7%, respectively. The antibiotic resistance rates of these isolates to cefotaxime, ceftazidime, and ciprofloxacin varied between 20% and 35%. However, these isolates were 100% susceptible to cefoxitin. Positive fragments were amplified from 59.8% (61/102) of the 102 S. flexneri isolates, the sizes of the sul1 and sul2 genes being 338 bp and 286 bp, respectively. The sequence alignment revealed the presence of the sul1 and sul2 genes encoding for dihydrofolate synthase. The carrying rate of the sul1 gene was 13.7% (14/102), and that of the sul2 gene was 48.0% (49/102). No target gene fragments were amplified from the 3 isolates resistant to sulfamethoxazole-trimethoprim. The sul3 gene and SXT element were not amplified from any of the isolates. The testing and statistical analysis showed that the resistance of the S. flexneri isolates to sulfamethoxazole-trimethoprim correlated to the sul1 and sul2 genes. The acquired antibiotic resistance genes sul1 and sul2 were closely associated with the resistance of the 102 S. flexneri isolates to sulfamethoxazole-trimethoprim.